Predictability of maximal oxygen consumption via beep test equations in collegiate field hockey players - Mathew, A.; Jones, M.; Young, W.; White, J. (The Journal of Strength and Conditioning Research, 2021)
Sport-specific fitness testing is necessary in order to determine an athlete's cardiorespiratory fitness and to monitor training program goals. Unfortunately, many athletic teams do not have access, funding, or personnel for laboratory testing, and could benefit from a valid method of field testing for aerobic fitness. Purpose: To determine if the multistage 20-meter shuttle-run test (BEEP) is a valid predictor of maximal aerobic capacity (Vo2 max) when compared to a laboratory treadmill ramp protocol assessment (GXT) of Vo2 max in National Collegiate Athletic Association (NCAA) Division I women collegiate field hockey players. A secondary purpose was to determine which predictive equation most accurately predicts Vo2 max. Methods: Sixty-five Division I women field hockey players (Mean ± SD; Age: 19.6 ± 1.2 years; Weight: 64.7 ± 6.1 kg; Body Fat: 24.5 ± 5.5%) completed both aerobic capacity assessments. The BEEP and GXT were separated by 48 hours and completed in randomized order. GXT tests were determined via treadmill ramp protocol of increasing intensity at one-minute intervals to volitional exhaustion, while collecting expired gases. BEEP tests results were determined by subjects running between cones separated by 20 meters, at an incrementally increasing pace, until the pace could no longer be maintained by the athlete. The following 6 predictive equations were used to estimate BEEP Vo2 max: Ramsbottom et al. Leger et al., Green et al. Chatterjee et al., St. Clair-Gibson et al., and Flouris et al. Repeated measures analysis of variance (RMANOVA) was used to compare BEEP equations and GXT Vo2 max (p = 0.05). Regression analysis was utilized to analyze the relationship between BEEP and GXT Vo2 max based off of the number of shuttles completed. Results: GXT Vo2 max was 46.4 ± 4.6 (mean ± SD) ml/kg/min, and BEEP Vo2 max (mean ± SD, ml/kg/min) for each predictive equation was: Ramsbottom; 46.5 ± 4.2, Leger; 50.2 ± 3.5, Green; 50.9 ± 4.0, Chatterjee; 45.7 ± 2.9, St. Clair-Gibson; 52.1 ± 3.6, Flouris; 46.3 ± 3.8. RMANOVA found a significant difference between Leger, Green, and St.Clair-Gibson (p < 0.001) BEEP predictive equations and GXT Vo2 max. Linear regression analysis found Ramsbottom to have the strongest relationship (r = 0.61, R2 = 0.37) while all other equations found r = 0.56, R2 = 0.31. Ninety-five percent confidence interval differences from the respective mean for each predictive equation: Chatterjee (±7.59), Ramsbottom (±7.78), Leger (±7.80), St. Claire-Gibson (±7.87), Flouris (±7.98), Green (±8.09). Conclusions: The 20-meter shuttle test can be a good predictor of GXT Vo2 max in NCAA Division I women collegiate field hockey players, but some predictive equations may be more accurate than others. Findings suggest that Ramsbottom's predictive equation most accurately predicts Vo2 max in this population. Practical Applications: The Ramsbottom equation is the most suitable proxy BEEP field test predictive equation for NCAA Division I women collegiate field hockey players aerobic assessment of Vo2 max. Practitioners that need to utilize the BEEP field test with female field hockey players should avoid the Leger, Green, and St. Clair-Gibson predictive equations.